Integrating Islamic Traditions and Educational Innovation in Modern Curriculum Management: A Study at Buntet Islamic Boarding School, Cirebon - Afifah Hidayati (Eduprof : Islamic Education Journal, 2026)
This study examines the integration of Islamic traditions and educational innovation within modern curriculum management at Buntet Islamic Boarding School in Cirebon. It aims to analyze how traditional Islamic education, rooted in classical texts and kyai authority, can be harmoniously combined with contemporary curriculum demands, including national standards and global competencies. Using a qualitative case study approach, data were collected through in-depth interviews with kyai, teachers, and stakeholders, classroom and pesantren activities observation, and analysis of curriculum documents. The findings reveal that curriculum management at the boarding school is structured through four key processes: (1) strategic planning that aligns the pesantren’s religious vision with societal needs; (2) implementation that integrates diniyah (religious) subjects, general academic knowledge, and technology-enhanced learning; (3) participatory evaluation involving internal and external stakeholders; and (4) deliberate innovations such as digital learning platforms, foreign language proficiency, and global orientation programs. This research contributes to the understanding of curriculum management in Islamic educational institutions by demonstrating a practical model of balancing sacred tradition with modernity. The study concludes that effective modern curriculum management in pesantren settings does not dilute Islamic authenticity but rather strengthens the relevance and competitiveness of graduates in the contemporary era, offering valuable insights for other traditional Islamic boarding schools facing similar modernization challenges.